2003
DOI: 10.1002/ajh.10431
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate in idiopathic and postpolycythemic myelofibrosis

Abstract: Imatinib mesylate targets the adenosine triphosphate (ATP)-binding sites of the protein tyrosine kinase domains associated with Bcr-abl, the platelet-derived growth factor (PDGF) and c-kit. In idiopathic myelofibrosis (IMF) PDGF is considered to be one of the growth factors responsible for the development of bone marrow fibrosis. Recently, it has been shown that imatinib has antifibrogenic effect on bone marrow fibrosis in chronic myelogenous leukemia. Treatment with imatinib alone in IMF has been associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…To date, five studies, including a total of 73 IM patients treated with imatinib, have been reported Cortes et al, 2003a;De Angelo et al, 2003;Hasselbalch et al, 2003;Stagno et al, 2004). Side effects were frequent and led to treatment withdrawal in a substantial proportion of patients.…”
Section: Imatinib and Other New Drugsmentioning
confidence: 99%
“…To date, five studies, including a total of 73 IM patients treated with imatinib, have been reported Cortes et al, 2003a;De Angelo et al, 2003;Hasselbalch et al, 2003;Stagno et al, 2004). Side effects were frequent and led to treatment withdrawal in a substantial proportion of patients.…”
Section: Imatinib and Other New Drugsmentioning
confidence: 99%
“…These cells are involved in the release of various elements that compose the extracellular matrix of BM, such as reticulin. IM has an independent anti-fibrotic effect on BM of CML patients, while IFN-a proves ineffective in patients with myelofibrosis at diagnosis (Kantarjianet al, 2005;Buescheet al, 2004;;Mello, 2004;;Klion et al, 2004;Suetterlin et al, 2004;Hasselbach et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib was administered at doses of 200-800 mg daily, but dropout rates were in excess of 50% across all trials. This was primarily because of a lack of tolerance secondary to edema, fatigue, and musculoskeletal pain [123][124][125][126][127][128][129]. Of note, Hasselbalch et al [128] reported proliferative effects in 9 of 11 patients who received imatinib at a dose of 400 mg daily, requiring hydroxyurea to manage leukocytosis and thrombocytosis.…”
Section: Signal Transduction Inhibitorsmentioning
confidence: 99%
“…This was primarily because of a lack of tolerance secondary to edema, fatigue, and musculoskeletal pain [123][124][125][126][127][128][129]. Of note, Hasselbalch et al [128] reported proliferative effects in 9 of 11 patients who received imatinib at a dose of 400 mg daily, requiring hydroxyurea to manage leukocytosis and thrombocytosis. Preliminary data on the efficacy of imatinib in CIMF reported in the European Myelofibrosis Network (EUMNET) trial documented an increase in the number of clonogenic megakaryocytic progenitors in bone marrow, suggesting that imatinib may restore megakaryocyte differentiation and thus be an effective treatment of thrombocytopenia in patients with CIMF [130].…”
Section: Signal Transduction Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation